De la lucha contra la discriminación laboral al aumento de la productividad: ¿puede la búsqueda de igualdad ir en línea con una búsqueda de eficiencia? - Villamar Cabezas , David (2018)
In this paper we model and measure a relationship between female labor participation—both in executive and managerial positions and in the total number of employees—and the labor productivity of firms. Our hypothesis is that there are comparativeadvantages by gender based on the neurobiological and psychological differencesbetween men and women. We use data from the annual sector surveys of the INEC(2011 to 2015) that contain firm level quantitative and qualitative information. Wefocus on the Hotels, Restaurants and Services Sector, where we explore the existenceof comparative advantages for women. The results show a positive effect of femalelabor participation in productivity and suggest that optimal levels of productivitywould be reached with a female labor participation of 58%. Likewise, we find that iffemale participation in both employed and managerial positions would increase by10 points, productivity would rise by 3.5%.